Opioidergic pathways and kisspeptin in the regulation of female reproduction in mammals - Uenoyama, Yoshihisa; Tsuchida, Hitomi; Nagae, Mayuko; Inoue, Naoko; Tsukamura, Hiroko (Frontiers in Neuroscience, 2022)
Endogenous opioid peptides have attracted attention as critical neuropeptides in the central mechanism regulating female reproduction ever since the discovery that arcuate dynorphin neurons that coexpress kisspeptin and neurokinin B (NKB), also known as KNDy neurons, play a role as a master regulator of pulsatile gonadotropin-releasing hormone (GnRH) release in mammals. In this paper, we first focus on the role of dynorphin released by KNDy neurons in the GnRH pulse generation. Second, we provide a historical overview of studies on endogenous opioid peptides. Third, we discuss how endogenous opioid peptides modulate tonic GnRH/gonadotropin release in female mammals as a mediator of inhibitory internal and external cues, such as ovarian steroids, nutritional status, or stress, on reproduction. Then, we discuss the role of endogenous opioid peptides in GnRH surge generation in female mammals.